2012
DOI: 10.1016/j.bcp.2012.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial superoxide mediates doxorubicin-induced keratinocyte apoptosis through oxidative modification of ERK and Bcl-2 ubiquitination

Abstract: Massive apoptosis of keratinocytes has been implicated in the pathogenesis of chemotherapy-induced skin toxicities, but the underlying mechanisms of action are not well understood. The present study investigated the apoptotic effect of doxorubicin (DOX) on HaCaT keratinocytes and determined the underlying mechanisms. Treatment of the cells with DOX induced reactive oxygen species (ROS) generation and a concomitant increase in apoptotic cell death through the mitochondrial death pathway independent of p53. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 40 publications
4
54
0
1
Order By: Relevance
“…A recent study has reported Ctip2 SUMOylation and ubiquitination in thymocytes (Zhang et al, 2012). In addition, ubiquitination and proteosomal degradation of anti-apoptotic Bcl2 protein has been observed in human dermal papilla cells and in keratinocytes (Luanpitpong et al, 2012;Luanpitpong et al, 2011). In this respect, Ctip2 may be similar to the transcription factor DNp63, which is also expressed predominantly in basal layer of epidermis, and is downregulated in differentiating keratinocytes by SUMO-conjugation and proteasomal degradation in response to high calcium (Vivo et al, 2009).…”
Section: Ctip2 Expression Is Regulated By Egf-egfr Signaling In Prolimentioning
confidence: 96%
“…A recent study has reported Ctip2 SUMOylation and ubiquitination in thymocytes (Zhang et al, 2012). In addition, ubiquitination and proteosomal degradation of anti-apoptotic Bcl2 protein has been observed in human dermal papilla cells and in keratinocytes (Luanpitpong et al, 2012;Luanpitpong et al, 2011). In this respect, Ctip2 may be similar to the transcription factor DNp63, which is also expressed predominantly in basal layer of epidermis, and is downregulated in differentiating keratinocytes by SUMO-conjugation and proteasomal degradation in response to high calcium (Vivo et al, 2009).…”
Section: Ctip2 Expression Is Regulated By Egf-egfr Signaling In Prolimentioning
confidence: 96%
“…Doxorubicin, a DNAdamaging agent, is believed to cause toxicity by inducing mitochondrial dysfunction and enhancing superoxide formation (33,34). Our previous study found that expression of BNIP3L, a regulator of mitophagy, significantly increased in colorectal cancer stem cells after doxorubicin treatment (5).…”
Section: Inhibition Of Mitophagy Enhances Drug Sensitivitymentioning
confidence: 99%
“…DOX has been shown to induce apoptosis in the Leishmania parasite (Singh and Dey, 2007;Luanpitpong et al, 2012) and, recently, was found to activate immune functions of macrophages and NK cells (Hussner et al, 2012). Immunointervention with antimonials, amphotericin B and DOX is known to improve VL (Murray et al, 2003a;Mukherjee et al, 2004), but toxicity remains a major concern.…”
Section: Introductionmentioning
confidence: 99%